Animal use in the late second millennium BCE in northern China: Evidence from Zaoshugounao and Zaolinhetan in the Jing River valley. (4th February 2020) - Li, Yue; Zhang, Chengrui; Wang, Zhen; Dou, Haifeng; Liu, Huan; Hou, Furen; Ma, Mingzhi; Qian, Yaopeng; Chen, Honghai
Abstract: Zooarchaeological research has contributed greatly to our understanding of animal use in the Bronze Age Central Plains in northern China, where remarkable social transformations occurred in the second millennium BCE. However, limited work has been done for the contemporaneous Jing and Wei River valleys, another crucial region in dynastic and imperial history of China that witnessed the political transition from the Shang Dynasty to the Zhou Dynasty (ca. 1050 BCE). In particular, the Zhou subsistence economy leading up to the emergence of the region as a centre of Zhou political authority is still poorly understood. Here, we present a zooarchaeological analysis of Zaoshugounao and Zaolinhetan, two sites associated with the predynastic Zhou, in present‐day central Shaanxi dating to before and around the Shang–Zhou transition. Results show that the Zaoshugounao and Zaolinhetan residents practiced intensive farming and animal husbandry in and around the settlements complemented by extensive caprine management on marginal lands. Along with other lines of archaeological evidence, our zooarchaeological data demonstrate that the economic developments in the Jing River valley in the late second millennium BCE, in terms of the diversified use of animal resources, underpinned the economic foundation behind the Zhou rise and their eventual conquest of the Shang.